ANALISIS PERAN GURU PENDIDIKAN JASMANI DALAM MODEL PEMBELAJARAN BERDIFERENSIASI PERMAINAN BOLA VOLI DI SDN SE-KECEMATAN TOWUTI - Aldianto; Ahmad; Kahar , Irsan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of physical education teachers in implementing a differentiated learning model in volleyball games at public elementary schools in Towuti District. This research employed a quantitative approach using a survey method. The sample consisted of 98 students and 5 physical education teachers. Data were collected through observation, in which the researcher identified several similarities and explanations from informants, including teaching methods, the implementation of differentiated learning models, as well as inhibiting and supporting factors in the application of the model. Supporting and inhibiting factors were mainly related to school facilities. Teachers conducted individual assessments based on students’ abilities. Differentiated learning methods are important to be applied in all classes to identify students’ individual abilities and to facilitate teachers in assessing student performance. Most students showed high interest in volleyball, as reflected in their scores, with the majority achieving scores between 80 and 95. Many students demonstrated strong potential and talent in sports, particularly in volleyball.